Platelet and Erythrocyte Indexes in Complex Regional Pain Syndrome Type I - Alparslan YETİŞGİN,; Ahmet TUTOĞLU,; Abdülhalik CİNAKLI,; Mahmut KUL,; Ahmet BOYACI, (Archives of Rheumatology, 2016)
Objectives: This study aims to compare the levels of platelet and erythrocyte indexes including mean platelet volume, platelet distribution width (PDW), and red blood cell distribution (RDW) values between complex regional pain syndrome (CRPS) type I patients and healthy controls to establish a marker of neuroinflammation that might be a potential factor involved in CRPS etiopathogenesis. Patients and methods: A total of 21 patients (14 males, 7 females; mean age 35.0±15.4 years; range 15 to 69 years) with a diagnosis of CRPS type I and 44 age- and sex-similar healthy controls (29 males, 15 females; mean age 35.8±8.5 years; range 16 to 53 years) were included in this study. Mean platelet volume, PDW, RDW, white blood count, hemoglobin, erythrocyte sedimentation rate, and C-reactive protein levels, and neutrophil to lymphocyte ratio and thrombocyte to lymphocyte ratio were compared between the patient and control groups. Results: No differences were noted between patient and control groups in terms of erythrocyte sedimentation rate and C-reactive protein levels, white blood cell, neutrophil, lymphocyte and thrombocyte counts, and neutrophil to lymphocyte and thrombocyte to lymphocyte ratios (all p>0.05). When compared with controls, patients had significantly higher mean corpuscular volume (p=0.019) and RDW (p=0.002) values, and a lower PDW level (p=0.006). Conclusion: Differences in PDW, RDW, and mean corpuscular volume values between patients and controls might support the potential role of neuroinflammation in the etiopathogenesis of CRPS type I. Prospective studies with larger sample sizes are warranted in the early detection and differential diagnosis of CRPS type I.